Hydrothermal Synthesis of Nanostructured Manganese Oxide as Cathodic Catalyst in a Microbial Fuel Cell Fed with Leachate - Yuan Haoran; Deng Lifang; Lu Tao; Chen Yong (The Scientific World Journal)
Much effort has been devoted to the synthesis of novel nanostructured MnO2 materials because of their unique properties and potential applications as cathode catalyst in Microbial fuel cell. Hybrid MnO2 nanostructures were fabricated by a simple hydrothermal method in this study. Their crystal structures, morphology, and electrochemical characters were carried out by FESEM, N2-adsorption-desorption, and CV, indicating that the hydrothermally synthesized MnO2 (HSM) was structured by nanorods of high aspect ratio and multivalve nanoflowers and more positive than the naturally synthesized MnO2 (NSM), accompanied by a noticeable increase in oxygen reduction peak current. When the HSM was employed as the cathode catalyst in air-cathode MFC which fed with leachate, a maximum power density of 119.07 mW/m2 was delivered, 64.68% higher than that with the NSM as cathode catalyst. Furthermore, the HSM via a 4-e pathway, but the NSM via a 2-e pathway in alkaline solution, and as 4-e pathway is a more efficient oxygen reduction reaction, the HSM was more positive than NSM. Our study provides useful information on facile preparation of cost-effective cathodic catalyst in air-cathode MFC for wastewater treatment.